Pendekatan Andragogi dalam Pembinaan Kecakapan Hidup Orang Dewasa Melalui Pendidikan Agama Kristen - Yuherlita Marneci; Yuel (Harati: Jurnal Pendidikan Kristen, 2024)
This research aims to provide an understanding of Andragogy as an art and science used to help adults learn, as well as how this concept is applied in Christian Religious Education (PAK) to develop life skills. PAK is a teaching process that is based on Biblical truth, centered on Christ, and relies on the power of the Holy Spirit. The life skills referred to in this research include practical and functional skills which aim to equip students to be able to solve various life problems, as well as proactively and creatively find solutions to overcome them. This research uses a qualitative method with a literature study approach, where data is obtained from various relevant literature sources. The research results show that the application of andragogy in PAK can help develop essential life skills for adults to face life's challenges more effectively. The conclusion of this research emphasizes the importance of integrating andragogy in PAK to empower students in everyday life.